2016
DOI: 10.3390/su8020157
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Tractor Selection: A Hybrid and Multi-Attribute Approach

Abstract: Usually, agricultural tractor investments are assessed using traditional economic techniques that only involve financial attributes, resulting in reductionist evaluations. However, tractors have qualitative and quantitative attributes that must be simultaneously integrated into the evaluation process. This article reports a hybrid and multi-attribute approach to assessing a set of agricultural tractors based on AHP-TOPSIS. To identify the attributes in the model, a survey including eighteen attributes was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…It is perceived that planning a series of factors to assist in optimizing the maintenance of agricultural tractors is a complex task. In the literature, it is possible to find different researchers that aim to facilitate the decision making of tractor purchases (MEHTA; SINGH; SELVAN, 2011;AMINI;ASSODAR, 2016;GARCÍA-ALCARAZ et al, 2016). However, for the management of agricultural tractors, with emphasis on the complete optimization of their maintenance, there is a lack of studies (POOZESH et al, 2012;SOPEGNO et al, 2016;AL-SUHAIBANI;WAHBY, 2017).…”
Section: Agricultural Tractor Maintenancementioning
confidence: 99%
“…It is perceived that planning a series of factors to assist in optimizing the maintenance of agricultural tractors is a complex task. In the literature, it is possible to find different researchers that aim to facilitate the decision making of tractor purchases (MEHTA; SINGH; SELVAN, 2011;AMINI;ASSODAR, 2016;GARCÍA-ALCARAZ et al, 2016). However, for the management of agricultural tractors, with emphasis on the complete optimization of their maintenance, there is a lack of studies (POOZESH et al, 2012;SOPEGNO et al, 2016;AL-SUHAIBANI;WAHBY, 2017).…”
Section: Agricultural Tractor Maintenancementioning
confidence: 99%
“…Grisso et al (2014) used tractor test data for selecting farm tractors. García-Alcaraz et al (2016) proposed a hybrid and multi-attribute approach to assess a set of agricultural tractors based on AHP and TOPSIS methods. Bol and Mohammed (2005) developed a mathematical model for farm machinery selection.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that rice has a higher priority compared to wheat and rapeseed, but the FAHP method showed more precision and reliability for the final prioritization of crops compared to the AHP method. AHP and TOPSIS methods were also used to select the appropriate tractor by García-Alcaraz et al (2016). To this end, 18 sales specialists and farmers were selected; their priorities were identified; some criteria, including the initial price, annual costs, fuel consumption, operator safety, and after-sales service, were selected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grisso et al (2014) used tractor test data for selecting farm tractors. García-Alcaraz et al (2016) proposed hybrid and multi-attribute approach to assess a set of agricultural tractors based on Analytic Hierarch Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. Bol and Mohammed (2005) developed a mathematical model for farm machinery selection.…”
Section: Introductionmentioning
confidence: 99%